Solvent Substitution: An Analysis of Comprehensive Hazard Screening Indices. - Debia, M.; Begin, D.; Gerin, M. (Journal of Occupational & Environmental Hygiene, 2011)
The air index (ψiair) of the PARIS II software (Environmental Protection Agency), the Indiana Relative Chemical Hazard Score (IRCHS), and the Final Hazard Score (FHS) used in the P2OASys system (Toxics Use Reduction Institute) are comprehensive hazard screening indices that can be used in solvent substitution. The objective of this study was to evaluate these indices using a list of 67 commonly used or recommended solvents. The indices ψiair, IRCHS and FHS were calculated considering 9, 13, and 33 parameters, respectively, that summarized health and safety hazards, and environmental impacts. Correlation and sensitivity analyses were performed. The vapor hazard ratio (VHR) was used as a reference point. Two good correlations were found: (1) between VHR and ψiair (ρ = 0.84), (2) and between IRCHS and FHS (ρ = 0.81). Values of sensitivity ratios above 0.2 were found with ψiair (4 of 9 parameters) and IRCHS (3 of 13 parameters), but not with FHS. Overall, the three indices exhibited important differences in the way they integrate key substitution factors, such as volatility, occupational exposure limit, skin exposure, flammability, carcinogenicity, photochemical oxidation potential, atmospheric global effects, and environmental terrestrial and aquatic effects. These differences can result in different choices of alternatives between indices, including the VHR. IRCHS and FHS are the most comprehensive indices but are very tedious and complex to use and lack sensitivity to several solvent-specific parameters. The index ψiair is simpler to calculate but does not cover some parameters important to solvents. There is presently no suitably comprehensive tool available for the substitution of solvents. A two-tier approach for the selection of solvents is recommended to avoid errors that could be made using only a global index or the consideration of the simple VHR. As a first tier, one would eliminate solvent candidates having crucial impacts. As a second tier, other parameters would be considered, with emphasis on the VHR.